ChemInform Abstract: Ruthenium‐Catalyzed Dehydrogenative C—H Borylation of Arenes with Pinacolborane. Issue 46 (October 2016) - Murata, Miki; Ueda, Yosuke; Hyogo, Mayu; Kohari, Yoshihito; Namikoshi, Takeshi; Watanabe, Shinji
Abstract: A ruthenium complex is shown to be efficient for the aromatic C—H borylation with pinacolborane.